Parity–Time Symmetry Synthetic Lasers: Physics and Devices. Issue 22 (11th September 2019) - Qi, Bingkun; Chen, Hua‐Zhou; Ge, Li; Berini, Pierre; Ma, Ren‐Min
Abstract: The invention of the laser has revolutionized modern science and engineering as well as our daily lives. Recently, a new class of lasers based on concepts borrowed from parity–time symmetry in quantum mechanics has emerged. Parity–time symmetry, initially applied to condensed matter systems, extends canonical quantum theory to non‐Hermitian quantum theory. The experimental exploration of parity–time symmetry in electronics is challenging; so by analogy, such concept is introduced in photonics where flexibility exists in realizing non‐Hermitian eigenstates involving optical gain and loss. Lasers intrinsically involve both gain and loss, which makes them the natural candidates to explore and exploit parity–time symmetry in photonics. Recent studies have demonstrated various novel laser devices based on parity–time symmetry, which show unique properties such as single mode lasing, chiral mode lasing, and exceptional point enhanced sensing. In this review, the fundamentals are introduced and recent advances in parity–time symmetric laser devices are discussed, furthermore an outlook on this emergent field is provided. Abstract : The emerging field of parity–time (PT) symmetric lasers is reviewed. Recent breakthroughs in PT single‐mode lasers, vortex lasers and enhanced sensing at exceptional points are presented. A brief discussion on topological lasers is also included. In the end, a prospective on this topic is given.